Design and Frabrication of Dump Truck Tilting System - Hariharan, R.; Lamare, Rimiki; Saha, Arindam; Das, Ranajit; Kumar, Amit; Ghosh, Sourjabrata (International Journal of Psychosocial Rehabilitation, 2019)
With the advancement of the transport technologies, companies are trying to find ways to find simpler and cost effective technologies. In today scenario dump trucks are used to transportation of materials till now they are operating by hydraulic cylinders. The hydraulic cylinders used for the dump truck tilting system are very long so that it can be lifted to a good height. It also requires a cylinder with greater diameter so that is can bear the weight of the materials in the truck. This requires a large space to house the cylinder and also the cylinder is prone to damages as it has to bear heavy loads. This not only occupies more space, but also increases the weight of the vehicle, which indirectly affects the fuel economy of the truck. Thus there is a surge to find possible methods for improving the mechanism of the dump truck hydraulics. This project proposes the idea of using a folding mechanism coupled with pneumatics to tilt the trolley of the dump truck. The system employs the use of a linkage hinged to together and a pneumatic cylinder is attached to the hinge. Thus when the pneumatic cylinder works in the forward direction, the linkages are stretched and when it is made to return, the linkages get folded up